The Influence of Work Motivation and Work Discipline on the Work Productivity of Employees at the Faculty of Mathematics and Natural Sciences, Manado State University - Naharia, Giovani; Masengi, Evi; Dilapanga, Abdul (Lafadz Jaya Publisher, 2023)
This research aims to determine and analyze the influence of work motivation and work discipline on work productivity partially and simultaneously. The method used in this research is descriptive quantitative with multiple regression analysis. The population in this study was 178 respondents with a sample of 119 respondents. The location of this research was carried out at the Faculty of Mathematics and Natural Sciences, Manado State University. Before the test was carried out, validity and reliability tests were carried out on 30 respondents and the results showed that all instruments were valid and reliable. The classical assumption test shows that everything meets the classical assumption requirements so that hypothesis testing can be carried out. Based on the hypothesis test, it was found that the Work Motivation variable (X1) with a value of tcount > ttable (6.029 < 1.658) with a positive value. So, there is a positive influence between variable X1 on Y, or in other words Ha is accepted and H0 is rejected. A significant value of 0.000<0.05 indicates that the influence value is significant. So overall the work motivation variable has a positive and significant effect on employee work productivity at the Faculty of Mathematics and Natural Sciences UNIMA. The research results show that the work discipline variable (X2) has a value of tcount > ttable (10.039 > 1.659) with a positive value. So, there is a positive influence between variable X1 on Y, or in other words Ha is accepted and H0 is rejected so that. A significant value of 0.000<0.05 indicates that the influence value is significant. So overall the work discipline variable has a positive and significant effect on employee work productivity at the Faculty of Mathematics and Natural Sciences UNIMA. The research results show that the value is significant at 0.0000 (sig 0.00000 < 0.05). This means showing that the regression equation obtained is reliable or that the model used is fixed. So, there is a joint or simultaneous influence between the Work Motivation and Work Discipline variables on the Work Productivity variable of employees at the Faculty of Mathematics and Natural Sciences UNIMA